О результатах аэродинамических расчётов осекольцевых конических диффузоров - Субботович, Валерий Петрович; Юдин, Юрий Алексеевич; Юдин, Александр Юрьевич; Темченко, Сергей Александрович (НТУ "ХПИ", 2016)
Представлены сравнительные расчётные исследования осекольцевых конических диффузоров с помощью CFD-программы. В расчетах использовались модели турбулентности, которые заложены в CFD-программу. Угол раскрытия наружного обвода диффузоров изменялся в диапазоне α = 11° –36° при изменении степени расширения диффузора n = 2–4. CFD-расчёты сравнивались с известной экспериментальной кривой Кляйна, которая делит плоскость (α–n) на две области: безотрывную и отрывную. Расчёты показали, что удовлетворительно моделировать безотрывные и отрывные течения в диффузорах подобного типа позволяет модель турбулентности (Spalart-Allmaras (S-A)).

Comparative design investigations of axiannular divergent cones were carried out using the CFD-software. Turbulence models built-in into the CFD-software were used for the computations, in particular Spalart-Allmaras (S-A), k–ω Shear Stress Transport (k–ω SST), V2F. The aperture angle of the external by-pass of cones varied in the range of α = 11°–36°, while the cone expansion degree varied as n = 2–4. The data of CFD computations were compared with the known experimental curve obtained by Klein and confirmed by Zariankin, which divides the plane (α–n) into two regions: unseparated flow and separated flow regions. The region above this curve represents the separated flow in the cone at any combination of parameters (α–n), and the region below this curve represents the unseparated flow.
On the data of aerodynamic computations of axiannular divergent cones
Keywords: кольцевой диффузор; степень расширения; угол раскрытия; осесимметричное течение; CFD-расчет; модель турбулентности; expansion degree; aperture angle; axially symmetric flow